Lexical Limits and Fringes in Medical Terminology - Briaukienė, Birutė (Respectus Philologicus, 2018)
The article analyses the attitudes of the students of Lithuanian University of Health Sciences (LSMU) regarding the use of loanwords in medical terminology. Many of the previously unacceptable and avoidable barbarisms used in the book of language tips “Lexicology: usage of loanwords” (published in 2013), became standard versions of the general language. Among such loanwords are the medical terms, which led to carrying out this research. Survey respondents were second-year students of the Faculty of Medicine of LSMU. The study involved 100 students. A list of 40 medical terms was specifically made for this research and was submitted to the students. The aim of this article is to research whether students are able to determine the ratio of a loanword to the norm of the standard language. The article raises the hypothesis that the students will be able to differentiate normative and non-standard loanwords. The analysis showed that 85.8% of respondents indicated loanwords being totally unacceptable and avoidable. Twice as many respondents reported that the loanwords, considered as side version of the norm, did not meet the requirements of the standard language norm. More than half (56.5%) of respondents indicated that loanwords, considered as an equivalent variant of the norm, did not meet the requirements of the standard language norm. The research hypothesis proved to be true.